The "Sete Fontes" groundwater system (Braga, NW Portugal): historical milestones and urban assessment - Antunes, Isabel Margarida Horta Ribeiro (2019)
Water resource assessment is essential to bring about sustainable growth of urban development and overall economic progress. Climate change and population growth pressure are important drivers in the available water resources. The crucial point of water management should be to promote an integrated water management in a river catchment and associated groundwater systems. The ancient drinking water system from Sete Fontes (Braga, northern Portugal) was built in the middle-eighteen century, and was the main water supply system of the city until 1913. This water system is located in a valley, with a NE-SW trend, promoting a favourable gentle slope to water gravity transport into the city. The Sete Fontes aquifer is characterized by Silurian metasediments intruded by Variscan granites, with two main fracturation trends - ENE-WSW and NW-SE. The mainly hydrogeochemistry is Na-Cl facies and locally Na-HCO3 facies. The groundwater is poorly mineralized, suggesting meteoric water contribution, with a relatively shallow circuit. During the Roman period, Sete Fontes system was probably the main source of water for the city. The economic, and demographic expansion of Braga lead to the increasing use of other water resources. Presently, the city primary delivery system is only supplied surface water from Cávado catchment. Natural groundwater characteristics from Sete Fontes shows that it is still suitable for human consumption and also to non-potable uses. The assessment also suggests that this is a sustainable water resource, that can constitute an important backup solution in case of failure of the main delivery system due to scarcity or catastrophe.